Synthesis and characterisation of lanthanide-doped nanocrystals as fluorescence biodetection probes - Liu, Ji. (2010)
Lanthanide-doped nanocrystal has emerged as a promising class of biolabelling probes for fluorescence biodetections with wide applications in many areas including forensics, medical diagnostics, DNA sequencing, immunoassay, flow cytometry and genetic analysis. This project demonstrates the synthesis of lanthanide-doped fluoride nanocrystals with two synthesis methods: the co-precipitation method and the liquid-phase method with metal-oleate precursors. In both methods, oleic acid (OA) was used as the surfactant to control the crystallisation process and to prevent aggregation of the nanocrystals. Through characterisation using common analytical techniques, including Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), X-Ray Diffraction (XRD) and fluorescent spectrometry, various conditions including reaction time, temperature, reactant concentration and solvent composition were studied for their influence on the properties of the nanocrystals.